Global change and Baltic coastal zones - Schernewski, Gerald; Hofstede, Jacobus; Neumann, Thomas (Coastal Research Library, 2011)
Climate change and ongoing transformation processes in economy and agriculture will have strong and multiple impacts in the Baltic region. In particular coastal zones face increasing hazards, e.g. due to sea level rise or changes in riverine nutrient loads and eutrophication. These changes also offer a wide range of new opportunities in the Baltic Region. Adaptation measures are needed but require a thorough and spatially differentiated understanding of underlying ecological, economic and social processes. Sixteen contributions by authors from eight countries give a comprehensive overview of these changes, their consequences and practical challenges with focus on coastal zones. Beside risks, the chances and opportunities of changes for the region are addressed and adaptation examples and strategies are given. The practitioners? perspective and their demands are integrated in the various contributions. Audience: This book is of interest to a wide readership. Scientists and researchers in the fields of environmental and coastal science and management, global change, geosciences, geography, and social sciences as well as employees at NGOs and policy makers will find valuable information in this book.